Update on Neonatal Isolated Hyperthyrotropinemia: A Systematic Review - Chiesa, Ana E.; Tellechea, Mariana L. (Frontiers in Endocrinology, 2021)
The purpose of this paper was to systematically summarize the published literature on neonatal isolated hyperthyrotropinemia (HTT), with a focus on prevalence, L-T4 management, re-evaluation of thyroid function during infancy or childhood, etiology including genetic variation, thyroid imaging tests, and developmental outcome. Electronic and manual searches were conducted for relevant publications, and a total of 46 articles were included in this systematic review. The overall prevalence of neonatal HTT was estimated at 0.06%. The occurrence of abnormal imaging tests was found to be higher in the persistent than in the transient condition. A continuous spectrum of thyroid impairment severity can occur because of genetic factors, environmental factors, or a combination of the two. Excessive or insufficient iodine levels were found in 46% and 16% of infants, respectively. Thirty-five different genetic variants have been found in three genes in 37 patients with neonatal HTT of different ethnic backgrounds extracted from studies with variable design. In general, genetic variants reported in the TSHR gene, the most auspicious candidate gene for HTT, may explain the phenotype of the patients. Many practitioners elect to treat infants with HTT to prevent any possible adverse developmental effects. Most patients with thyroid abnormalities and/or carrying monoallelic or biallelic genetic variants have received L-T4 treatment. For all those neonates on treatment with L-T4, it is essential to ensure follow-up until 2 or 3 years of age and to conduct medically supervised trial-off therapy when warranted. TSH levels were found to be elevated following cessation of therapy in 44% of children. Withdrawal of treatment was judged as unsuccessful, and medication was restarted, in 78% of cases. Finally, data extracted from nine studies showed that none of the 94 included patients proved to have a poor developmental outcome (0/94). Among subjects presenting with normal cognitive performance, 82% of cases have received L-T4 therapy. Until now, the precise neurodevelopmental risks posed by mild disease remain uncertain.